A Smart Green Data Center of Energy Conservation in Cloud and Mobile Cloud Computing - Sudha, MR; Sumathi, C.P (International Journal of Computer Sciences and Engineering, 2019)
This paper focused to green system of the small data centers with sustainable energy power generation. The estimation must start with a baseline view of power consumption in every part of the data center. The primary vital issues of data centers are increasingly under intervention of their energy consumption and operations. This paper takes first step toward exploring green data centers powered by renewable energy system that include base load power supply, intermittent power supply and backup energy storage systems. The required energy assists in an embryonic attitude of data centers being saved energy with a "greener" consequence. Data centers are the factories of the digital world and the cloud is coming back to earth that ethereal place where data is being stored. The convention of renewable energy resources has been the vital role in our future development of modern technology and cloud computing is the fastest evolving paradigm of the modern age of computers. This requires more and more remote host machines such as servers. Naturally, data centers are required large amounts of energy to power the growing demand. Now, data centers are turning to energy-efficient data facilities to cut costs and green power for their operations. This paper presents small-scale routing algorithm used energy consumption by instead of using conventional energy, thus increasing the effective performance up gradation of the virtual data center. We bring new thought in energy saving of the data centers. This presents the technological way of power consumption in the records of data center.